Roles of Ti-Based Catalysts on Magnesium Hydride and Its Hydrogen Storage Properties - Chengshang Zhou; Jingxi Zhang; Robert C. Bowman; Zhigang Zak Fang (Inorganics, 2021)
Magnesium-based hydrides are considered as promising candidates for solid-state hydrogen storage and thermal energy storage, due to their high hydrogen capacity, reversibility, and elemental abundance of Mg. To improve the sluggish kinetics of MgH2, catalytic doping using Ti-based catalysts is regarded as an effective approach to enhance Mg-based materials. In the past decades, Ti-based additives, as one of the important groups of catalysts, have received intensive endeavors towards the understanding of the fundamental principle of catalysis for the Mg-H2 reaction. In this review, we start with the introduction of fundamental features of magnesium hydride and then summarize the recent advances of Ti-based additive doped MgH2 materials. The roles of Ti-based catalysts in various categories of elemental metals, hydrides, oxides, halides, and intermetallic compounds were overviewed. Particularly, the kinetic mechanisms are discussed in detail. Moreover, the remaining challenges and future perspectives of Mg-based hydrides are discussed.